2013
DOI: 10.1002/eat.22187
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic alliance in two treatments for adults with severe and enduring anorexia nervosa

Abstract: The results suggest that therapeutic alliance can be effectively established in the treatment of SE-AN and may be relevant for treatment response, particularly in late treatment, on some aspects of ED and depressive symptomatology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 26 publications
2
36
0
1
Order By: Relevance
“…However, current findings on the role of the therapeutic alliance in the treatment of AN are inconsistent (Brown, Mountford, & Waller, 2013;Stiles-Shields et al, 2013). Interestingly, the subscale sense of autonomy loaded on this fourth dimension rather than on basic need satisfaction which we would expect given current theory.…”
Section: Discussionmentioning
confidence: 56%
“…However, current findings on the role of the therapeutic alliance in the treatment of AN are inconsistent (Brown, Mountford, & Waller, 2013;Stiles-Shields et al, 2013). Interestingly, the subscale sense of autonomy loaded on this fourth dimension rather than on basic need satisfaction which we would expect given current theory.…”
Section: Discussionmentioning
confidence: 56%
“…In addition, those with more severe symptoms, depression, older age and the purging subtype of anorexia nervosa appeared to benefit more from CBT [24]. Within therapy predictors of outcome included the quality of the therapeutic alliance [28] and improved eating disorder symptoms and BMI [25].…”
Section: Randomized Controlled Trials Of Treatmentmentioning
confidence: 94%
“…Of the studies pertaining to the treatment of adult anorexia nervosa, two studies demonstrate support for the existence of an alliance-outcome association (Sly, Morgan, Mountford, & Lacey, 2013;Stiles-Shields et al, 2013). Sly and colleagues (2013) found that changes in the therapeutic alliance do not predict premature treatment termination.…”
Section: Anorexia Nervosamentioning
confidence: 96%